Reliability analysis using exponentiated Weibull distribution and inverse power law - Mendez Gonzalez, Luis Carlos (2019)
Today in reliability analysis, the most used distribution to describe the behavior of devices is theWeibull distribution. Nonetheless, theWeibull distribution does not provide an excellent fit to lifetime datasets that exhibit bathtub shaped or upside-down bathtub shaped (unimodal) failure rates, which are often encountered in the performance of products such as electronic devices (ED). In this paper, a reliability model based on the exponentiated Weibull distribution and the inverse power law model is proposed, this new model provides a better approach to model the performance and fit of the lifetimes of electronic devices. A case study based on the lifetime of a surface-mounted electrolytic capacitor is presented in this paper. Besides, it was found that the estimation of the proposed model differs from theWeibull classicalmodel and that affects the mean time to failure (MTTF) of the capacitor under analysis.